Decision Making About Voter Eligibility and Social Assistance Recipients in Bandung - Supriadi, Hari; Rozahi Istambul, Muhammad; Hamdani, Dani; Amalia, Endang; Parlindungan, (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to create alternative media in the form of application design in managing population data and present information related to population data, such as citizens who have the right to vote in the regional head election process, and the head of state can then present information related to citizens entitled to receive social assistance from the government local. Designing alternative media, the method used is prototyping as an alternative media development model, which is related to population data. As for the steps, among others: listening to customers, designing, and evaluating prototypes. The findings of this research can provide convenience for management both at the RT and RW levels in managing population data and can easily present information related to population rights, both related to election data and those entitled to receive social assistance from local authorities. Business processes carried out in the RW/RT Riung area of Bandung Estate. Further observations at Riung Bandung Estate are needed in the future to provide information related to the data center (database) of a citizen. In short, it is very important for Riung Bandung, especially at the RT/RW level, especially as a medium that can provide convenience in managing citizen data centers and presenting information entitled to participate in elections and receiving social assistance, as well as providing the information needed by citizens online. This research is expected to provide a different pattern as an alternative medium in the form of online information presentation, which can make it easy for residents to find out information related to the data center of a citizen.